(untitled) (Research, Society and Development, 2020)
Realistic Simulation is a tool that has been widely used in health education, developing skills such as: teamwork, decision making and communication. It contributes to learning by allowing students to experience reality, in a safe and pedagogically planned environment. Objective: To compare Primary Health Care learning between Medical Students who attended an lecture and those who underwent Realistic Simulation. Method: Quasi-experimental research, carried out with Medical Students. The sample consisted of 144 students who were organized into two groups: control and experimental. The research had three stages: pre-test, class development (lecture or Realistic Simulation) and post-test. Data collection took place from August to September 2019. A data collection instrument was used, composed of objetive questions. Results: The mean of correct answers in the pre-test was 7.05 and 7.35 in the experimental and control groups, respectively. The average of correct answers between the post-test was 7.62 and 8.05 in the experimental and control groups, respectively. Conclusion: Cognitive learning was similar with the use of the Realistic Simulation technique when compared to the traditional teaching methodology, however Realistic Simulation develops other skills, such as self-confidence and critical thinking, teamwork, leadership, in addition to being an incentive students for self-learning.